Analisis Kesalahan Penyusunan Kalimat Efektif Pada Laporan Praktikum Kimia Fisika - Gabriel Firgiane; Miranda Angeline; Adinda Fatin; Shabrina Nur; Raihan Zaky; Eni Nur Hayati (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Language serves as a means of oral and written communication used by humans to interact. The use of proper and correct language, especially Indonesian language, is a necessity. In writing descriptive essays, it is important to use formal and effective sentences to ensure that the writer's message is easily understood by the readers. Based on these reasons, the researcher is interested in understanding and examining more deeply the errors in constructing effective sentences made by students. The focus of this research is on the reports of physical chemistry experiments written by students of Universitas Pembangunan Nasional (UPN) Veteran East Java. The research method used in this study is a descriptive method. In this research, the analyzed information is the errors in constructing effective sentences in the reports of physical chemistry experiments by students from UPN Veteran East Java in 2023. From the data analysis of the reports of physical chemistry experiments by UPN Veteran East Java students, it is revealed that there are several errors in the writing of those reports. The errors found include the breakdown of the main ideas, the combination of elements in sentences, the excessive use of words, spelling errors, irregular sentence structures, and incompleteness in the elements of effective sentences. However, to reduce these kinds of errors, there are several steps that can be taken: (1) students are advised to actively ask questions to their professors or peers regarding the mistakes they have made, (2) applying the knowledge they have learned, especially in producing papers as scientific works, (3) students need to make efforts to enhance their understanding and experience through reading books and scientific works so that they can develop new knowledge and approach perfection in writing scientific works by avoiding possible errors.Â